Effectiveness of hand-arm bimanual intensive training on upper extremity function in children with cerebral palsy: A systematic review. (March 2020) - Ouyang, Rang-Ge; Yang, Chieh-Ning; Qu, Ya-Lan; Koduri, Manohar Prasad; Chien, Chi-Wen
Abstract: Objective: To systematically review the effectiveness of Hand-Arm Bimanual Intensive Training (HABIT) on upper limb function in children with cerebral palsy. Methods: Six databases (MEDLINE, CINAHL, PubMed, Embase, Cochrane Library, and PsycINFO) were searched for HABIT-related studies published in English between 2007 and 2017. The methodological quality of the included studies was classified based on the Levels of Evidence of the American Occupational Therapy Association guidelines. If the included studies were randomized controlled trials (RCTs), the methodological quality was evaluated using the Revised Cochrane risk of bias tool. Cohen's d effect sizes were computed and synthesized to assess the effectiveness. Results: Among 646 studies, 15 fulfilled the inclusion criteria. Eleven studies were RCTs, 64% of which were rated as having a high risk of bias; one was a quasi-RCT, one was a retrospective study, and two were longitudinal studies. Nearly half of the included studies used HABIT for 6 h a day for three consecutive weeks (totaling 90 h), and some studies used different doses/schedules or added training components to HABIT. Synthesis of the results demonstrated a significantly small effect size ( d = 0.36, P = 0.017) for improving upper limb function immediately after the interventions, and the improvements were maintained at follow-up. Similarly, significantly moderate or large effect sizes were found for self-care function ( d = 0.52, P = 0.003) and goal improvements ( d = 1.78–2.28, P < 0.001). Conclusion: This review supports the effectiveness of HABIT as an intervention for improving upper limb function in children with cerebral palsy. Highlights: HABIT is an intensive child-friendly training for children with cerebral palsy. HABIT improves bimanual ability and unilateral dexterity. HABIT additionally improves self-care function and functional goal performance.